Pemanfaatan Tepung Kulit Pisang (Musa paradisiaca) Dengan Variasi Penambahan Gliserol Sebagai Bahan Alternatif Pembuatan Bioplastik Ramah Lingkungan - Munawaroh, Amin; , Dra. Suparti, M.Si (2015)
USE OF FLOUR BANANA SKIN (Musa paradisiaca) WITH THE ADDITION OF VARIATION GLYCEROL AS BIOPLASTICS MAKING MATERIALS ENVIRONMENTALLY FRIENDLY ALTERNATIVE 1) Amin Munawaroh, 2) Suparti, M.Si., 1) Student alumnus, 2) Lecturer Biology Education Department, Faculty of Education and Teacher Training, Muhammadiyah University of Surakarta, 2015. ABSTRACT Banana peel is waste that has not been widely used by the community and have a fairly high starch content. The starch content can be processed into bioplastics by adding additional material (Plasticizer) so that more elastic plastic. Bioplastics are plastics that can be degraded by microorganisms in a faster time than the synthetic plastics. This study aims to determine the effect of variations in the composition of a banana skin starch and glycerol volume to the value of tensile strength and elongation values (elongation at break) on bioplastics from banana peels. This study uses a completely randomized design two factors: factor 1: Composition flour banana peel 2g, 3g, 4g, and a factor of 2: Volume 3ml glycerol, 4m, 5ml. Based on the two-lane test ANOVA analysis showed that there is influence of the addition of a banana skin flour composition and volume of glycerol to the values of tensile strength and elongation values on bioplastics. From the test results, the best treatment is the banana skin starch composition and volume of glycerol 3ml 4g (T3G1) with a value of tensile strength of 10.51 kg / cm2 and 17.33% elongation value. Keywords: Bioplastics, Glycerol, Banana Skin, Plasticizer.